(untitled) (American International Journal of Economics and Finance Research, 2021)
The aim of the present study is to review and develop a conceptual model of the relationship between career performance attributes, career path, and employee performance of the public sector in Oman. The study used online empirical recourses by the name of career performance attributes, career path, and employee performance in different online database sources such as Google Scholars, Springer Link, Wiley, Science Direct, JSTOR, Emerald full text, Scopus, and EBSCO HOST, etc. The review study summarized that Job satisfaction is the positive emotion result from the appraisal of job experience and fulfillment of employee needs. The study also found that job satisfaction can gain high performance whereas the dissatisfied performance of employees yields low employee performance. Moreover, the study also observed that career development and life changes have become very challenging for working women and there are numerous studies targeted towards gaining a better understanding of this issue, its consequences and the significance of these challenges. Finally, the research develops a conceptual framework that is to be followed in order to analyze the various elements and aspects. The framework has been designed by considering the various variables and their intricacies in particular relation to the subject matter of the research work in Oman and the regions.